The misuse of Tramadol among children and youth and the need for having efficient policy and laws enforcement - Buasumlee, Benjaporn; Boonyarattanasoontorn, Jaturong (Interdisciplinary Research Review, 2020)
Tramadol, classified as a dangerous drug, is spreading among children and youth in many countries. This article aims to review and examine the misuse of Tramadol, the regulatory policies, and the gab of knowledge to be filled by conducting research. A literature review is employed to collect information. Based on the finding of researches and analysis, Tramadol is spreading in some African and West Asian countries. It is sold in general drug stores in Thailand on social media or in an internet caf´e. Children and youth combine tramadol with a drink that has caffeine which is harmful to their physical and mental health. It is an urgent need to conduct the research and suggest the government to issue the effcient policy and law enforcement.